The Value Added Tax and Growth : Design Matters - Acosta Ormaechea, Santiago (IMF Working Papers; Working Paper, 2019)
Does the design of a tax matter for growth? Assembling a novel dataset for 30 OECD countries over the 1970-2016 period, this paper examines whether the value added tax (VAT) may have different effects on long-run growth depending on whether it is raised through the standard rate or through C-efficiency (a measure of the departure of the VAT from a perfectly enforced tax levied at a single rate on all consumption). Our key findings are twofold. First, for a given total tax revenue, a rise in the VAT, financed by a fall in income taxes, promotes growth only when the VAT is raised through C-efficiency. Second, for a given VAT revenue, a rise in Cefficiency, offset by a fall in the standard rate, also promotes growth. The implication is thus that in OECD countries broadening the VAT base through fewer reduced rates and exemptions is more conducive to higher long-run growth than a rise in the standard rate.